2022
DOI: 10.1075/jslp.22013.tel
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling professional competence and foreign accent

Abstract: This study examined listeners’ evaluations of first (L1) and second language (L2) English speech in work-related contexts. Ninety-six English-speaking listeners from Calgary rated audio recordings of 12 English speakers (6 L1 English, 6 L1 Tagalog) along three continua capturing one professional (competence), one experiential (treatment preference), and one linguistic (comprehensibility) dimension. The audio recordings additionally differed in terms of job prestige (high vs. low) and performance level (high vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In addition to that, teachers generally revealed that boys don't like English language teachers. This is in line with the reporting of Sprouse et al (2018); Teló et al (2022), who all reported that some boys tend to have a dislike for English language teachers. The administrators also reported that some teachers also witch-hunt certain students.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to that, teachers generally revealed that boys don't like English language teachers. This is in line with the reporting of Sprouse et al (2018); Teló et al (2022), who all reported that some boys tend to have a dislike for English language teachers. The administrators also reported that some teachers also witch-hunt certain students.…”
Section: Discussionsupporting
confidence: 91%
“…Although an accent has nothing to do with one’s level of medical knowledge, it seemingly indicates trustworthiness, which is deemed a desirable quality in a doctor (Baquiran and Nicoladis, 2020). This example highlights how accentism operates as a type of individual linguistic profiling and bias in which workers are evaluated in terms of how they sound (Teló et al. , 2022).…”
Section: Theorizing Accentism: From the Interpersonal To The Institut...mentioning
confidence: 99%
“…Although an accent has nothing to do with one's level of medical knowledge, it seemingly indicates trustworthiness, which is deemed a desirable quality in a doctor (Baquiran and Nicoladis, 2020). This example highlights how accentism operates as a type of individual linguistic profiling and bias in which workers are evaluated in terms of how they sound (Tel o et al, 2022). Moreover, from a social-cognitive-career-theoretical (SCCT) perspective, accentism threatens workers' sense of self-efficacy in finding or maintaining employment as having an "undesirable accent" can be believed to be a natural career obstacle (Lent et al, 2002;Yakushko et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In light of this, Teló et al (2022) investigated how foreign accents are unfavorably compared to "White" accents. In their research, they studied listeners' evaluations of first (L 1 ) and second (L 2 ) language speakers of English.…”
Section: Literature Reviewmentioning
confidence: 99%